2013
DOI: 10.1007/s13191-012-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Compressive Strength and Flexural Strength of Conventional Core Materials with Nanohybrid Composite Resin Core Material an in Vitro Study

Abstract: Several dental materials have been used for core build-up procedures. Most of these materials were not specifically developed for this purpose, but as a consequence of their properties, have found application in core build-up procedures. Improvements in composites and the development of nanocomposites have led to their use as a core build up material due to their superior mechanical properties, optical properties and ease of handling. However it is not clear if they have better mechanical properties than the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 37 publications
3
43
0
4
Order By: Relevance
“…Flexural strength is the only mechanical property specified by the ISO 4049 standard for composite restorative materials, which requires minimal values of 80 MPa for occlusal tooth surface restorations and 50 MPa for others [ 62 ], so all investigated materials meet these requirements. The obtained results were additionally comparable to other materials with similar matrix or filler concentrations [ 4 , 106 , 107 , 108 ]. A parallel situation was noted for flexural moduli [ 109 ], the values of which are not defined by the standard and may be diversified for different clinical situations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Flexural strength is the only mechanical property specified by the ISO 4049 standard for composite restorative materials, which requires minimal values of 80 MPa for occlusal tooth surface restorations and 50 MPa for others [ 62 ], so all investigated materials meet these requirements. The obtained results were additionally comparable to other materials with similar matrix or filler concentrations [ 4 , 106 , 107 , 108 ]. A parallel situation was noted for flexural moduli [ 109 ], the values of which are not defined by the standard and may be diversified for different clinical situations.…”
Section: Discussionsupporting
confidence: 79%
“…One of the strategies allowing reconstruction of the teeth structure is using direct restorative materials, which are shaped intraorally to create restorations directly in teeth cavities [ 3 ]. Currently, the most common of them are photopolymerizable resin-based composites, introduced few decades ago as a substitute for amalgams [ 4 ]. This type of material is also considered to be the most prospective, which has resulted in a growing number of new products on the market and numerous investigations in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Flexural strength (FS), defined as the failure stress of a material as measured in bending, is generally considered a meaningful mechanical property for brittle materials that are much weaker in tension than in compression. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with other studies that found no statistically significant difference in the compressive strength results of nanofilled and nanohybrid commercial composite types (18,19) . Another study found that nanocomposite showed higher compressive strength values than dental amalgam and resin modified glass ionomer (20) . From the above results, it could be emphasized the success of the experimental nanocomposite to be used as dental core material in terms of compressive strength performance.…”
Section: Discussionmentioning
confidence: 99%